Review Old Effect Study On Quality of Irrigation Water and Physical Properties Andosol Soil And Plant Growth Soybean (Glycine max) - Siti Alfi Syahrin; Sumono Sumono; Adian Rindang (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Soybean plants were flooded for a long time will inhibit the growth and yield of soybean. For that, there should be proper drainage, in order to cope with flooding due to decreased plant productivity. This study aimed to assess the effect of long inundation on the growth of soybean plants using Andosol soil. Measure variable is water quality, physical properties soil and soybean production. The results indicate that water quality parameters waterlogged conditions 3 days whereas the dissolved oxygen, in the affect the physical properties of soil is the pH of the soil, with soybean production (2 plants / pot) 96 pods. On the waterlogged conditions until wilted/dead water quality parameters  affect the dissolved oxygen and pH of the water, in the affect the physical properties of soil is the pH of the soil, with soybean production 36 pods. On the condition of field capacity water quality parameters and physical properties of soil in accordance with the terms optimal growth of soybean plants, with soybean production 241 pods. Keywords: water quality, soil physical properties of Andosol, the growth of soybean plants